Підвищення ефективності розподілу ресурсів телекомунікаційної мережі шляхом зміни маршрутів передавання даних - Бугиль, Б. А.; Климаш, М. М.; Лаврів, О. А.; Демидов, І. В. (Проблеми телекомунікацій, 2012)
The article deals with reasons why the planned network resource is not used completely. The main attention is paid to the dynamic routing protocol, which doesn’t consider the current load of local network segments according to the principle of its functioning. In the paper local segments loading considers with existence of a constant flow to reduce the computational complexity of the proposed method. The method is proposed in the work to maximize the use of network resources and resource allocation improving based on alternative routes variation through less loaded local segment. The proposed method is implemented as a simulation model in Matlab. It allows making decision on routes variation based on introduced resource allocation efficiency index. The article shows results of two experiments on the proposed method to determine its adequacy. The task of the first experiment is to determine the effectiveness of the method to vary the network resources allocation for simple network structure. The second experiment compares the value of resource allocation efficiency index with load balancing according to the protocol EIGRP and the one with route replacement. The proposed method replaces dynamically defined routes to alternative that maximizes the efficient use of shared network resource.
Keywords: граф; показник ефективності; розподіл ресурсів